THE EFFECT OF TAX INSPECTION AND LAW ENFORCEMENT ON TAX EVASION AT THE SOUTH BATAM PRIMARY T AX SERVICE OFFICE - Asnita Simbolon; Vargo Christian L. Tobing (SEAN Institute, 2023)
The cause of the frequent practice of Tax Evasion is the lack of Law Enforcement, therefore the perpetrators feel that the actions they will take are not detected, and if they are detected, it is very likely that the law obtained is relatively light. To reduce the level of Tax Evasion Practices in Indonesia, the role of the government is very important to prevent officials and tax evaders from practicing Tax Evasion for any reason. This research uses a quantitative type of research. The results of this study showed that there was no significant influence between tax evasion conducted by taxpayers , besides that there was a significant influence between tax inspections on tax evasion carried out by taxpayers. Finally, from this study, there is a simultaneous influence between tax inspection and law enforcement on tax evasion at KPP Pratam Batam. The size of the tax evasion carried out by taxpayers is determined by law enforcement and also tax inspections carried out by KPP Pratama Batam.